Atypical Colonoscopic Presentation of Lymphocytic Colitis Mimicking Hyperplastic Polyposis Syndrome - Iqbal, Umair (Cureus, 2018)
Lymphocytic colitis is a chronic inflammatory disease of colon usually presented in middle age female as chronic watery diarrhea. Diagnosis is made on biopsy as colonoscopy usually revealed normal appearing colonic mucosa. We present here an unusual case of a 25-year-old female with past medical history of asthma was evaluated for one year of non-bloody watery diarrhea. The symptoms started after a course of antibiotics for upper respiratory tract infection a year back. The serum chemistries, including liver enzymes, were unremarkable. Stool culture, ova, and parasites were unremarkable. Stool Clostridium difficile was also negative. Celiac disease antibodies were unremarkable. Stool occult blood test was positive. The patient underwent colonoscopy for the evaluation of chronic diarrhea and revealed multiple polyps throughout the colon with inflamed surfaces which were biopsied. The concern was for hyperplastic polyposis syndrome. Genetic testing for adenomatous polyposis gene was done and came back negative. Biopsy from polyps revealed lymphocytic colitis. The patient was started on budesonide which resulted in marked improvement in her symptoms. Our case highlighted an atypical endoscopic finding of lymphocytic colitis which mimic hyperplastic polyposis syndrome.